Proportion of hepatitis C virus antibodies in icteric patients - Al-Omar S. Layla; Mukhlis A. Faiza; Al-Khayatt Ramzia (College of Pharmacy / Mustansiriyah University, 2004)
A total of 1783 sera from icteric patients (988 male & 795 female), their ages ranged 8-54 years, were tested for the presence of viral hepatitis markers (hepatitis A, B, and C), using the available diagnostic kits (enzyme linked immunosorbant assay). 300 donor sera were also tested as matched control. Among the icteric patients 859 (48,2%) had evidence of acute hepatitis A (HA), 499 (28%) were found to be infected with hepatitis B (HB), and hepatitis C virus (HCV-Ab) was detected in 8.2% of patients that confirmed by recombinant immunoblot assay. The results indicated that the maximum HCV seroprevalence was found in patients more than 30 years old, and there was no difference in the chance of infection in both sexes. The main route of HCV transmission was observed in icteric patients who had received blood, and those underwent surgical intervention. These reflect the fact that some of transfused blood may contain HCV that could not be detected by routine serological tests used in Blood Bank. There is a need to identify HCV carriers and the increased awareness of medical and paramedical personnel regarding the risk of transmitting the disease iatrogenically. Furthermore the need to document the risk of nosocomial transmission and highlight the crucial role of molecular sequence based phylogenetic analysis of cloned viral isolates in the investigation of HCV infection.